Designig data-intensive web apllications - Fraternali, Piero; Ceri, Stefano (San Francisco : Morgan Kaufmann Publishers, 2003)
Contenido: Technologies for web applications. HTTP and HTML. SQL: the structured query language for relational detabases. Models for designing web apllications.Design of web apllications. Implementation fo web applications